Deletion of p38γ attenuates ethanol consumption- and acetaminophen-induced liver injury in mice through promoting Dlg1 - Hu Shuang; Yao Yan; Wei Ze-yuan; Wang Shu-xian; Wu Yin-cui; Hu Ying; Yang Chen-chen; Min Jing-li; Li Liang-yun; Zhou Hong; Yang Jun-fa; Li Jun; et al. (Acta Pharmacologica Sinica; Vol 43, No 7 (July 2022): Acta Pharmacologica Sinica, 2022)
Acetaminophen (APAP) is one of the major causes of drug-induced acute liver injury, and ethanol may aggravate APAP-induced liver injury. The problem of ethanol- and APAP-induced liver injury becomes increasingly prominent, but the mechanism of ethanol- and APAP-induced liver injury remains ambiguous. p38γ is one of the four isoforms of P38 mitogen activated protein kinases, that contributes to inflammation in different diseases. In this study we investigated the role of p38γ in ethanol- and APAP-induced liver injury. Liver injury was induced in male C57BL/6 J mice by giving liquid diet containing 5% ethanol (v/v) for 10 days, followed by gavage of ethanol (25% (v/v